Analisis Perilaku Konsumen terhadap Keputusan Pembelian Buah-Buahan di Moena Fresh Bali - PADMI, NI MADE SRI KESARI DHARMA; DEWI, RATNA KOMALA; ANGGRENI, I.G.A.A. LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
The Analysis of Consumers’ Behavior Against The Decision on Purchasing Fruits in Moena Fresh This research aimed to (1) analyze the process of decision making in purchasing fresh fruits in Moena Fresh, (2) analyze the factors which influence the consumers in deciding to purchase fruits in Moena Fresh. The data analysis method that were used were descriptive analysis to find out the process of decision making in purchasing the fruits and factor analysis to analyze the factors which influenced the consumers in deciding to purchase the fruits in Moena Fresh. The results showed some of the steps that consumer passing through before purchasing, those were the recognition of needs, search of information, evaluation of alternatives, purchase, and post-purchase. Factors that influenced the consumers in deciding the purchasing of fresh fruits in Moena Fresh include external factor and internal factor. External factor that is environment factor that involves variable of freshness of the fruits, fruit hygiene, packaging, price of fruits, cleanliness of the rack, service of the store employees, store temperature, and the aroma of the store. Internal factor that is psychological factor that involves variable of the types of the fruits; and also individual differences factor consists of the income of the consumers. Suggestions that can be given that Moena Fresh pay attention to the availality of fruit on order to avoid a product void and consider other factors such as, advertising and situation of consumer psychology.